Preparation and Antifouling Properties of Poly(vinyl alcohol)-co-Poly(acrylamide) Macroporous Hydrogels - Cong, Weiwei; Xiao, Ling; Wang, Ke; Chen, Zhengtao; Yu, Xueyan; Gui, Taijiang (Asian Journal of Chemistry, 2013)
In recent years, high-efficiency and non-toxic antifouling techniques are predominant in view of environmental protection and public safety. In this paper, biomimetic antifouling technique was carried out. Poly(vinyl alcohol)-co-poly(acrylamide) (PVA/PAM) macroporous hydrogels were synthesized by porogenic technique using PEG200, PEG1000 and PEG6000 as pore forming agents, polyvinyl alcohol and acrylamide (AM) as raw materials and while polyvinyl alcohol could enhance the mechanical strength of macroporous hydrogels. Poly(ethylene glycol) with different molecular weight made different pore structure, when macroporous hydrogel had a porous structure with a pore size mostly between 10-30 μm with PEG1000 and possessed good mechanical strength which was suitable for the culture medium of marine bacterium. Further, we extracted Kytococcus sedentarius which had bacteriostasic activity from marine microbial biofilm. PVA/PAM macroporous hydrogel with Kytococcus sedentarius in it made biomimetic biofilm and their antifouling performance were tested in the sea for 5 months. It is suggested that the biomimetic biofilm with only a little green alga on it for 5 months demonstrated better antifouling properties.